The Climate Change Impact on Water Crisis and Water Resource Sustainability by Using Nanoparticle in Gaza: Economic Solutions & Strategies Review - Puspita Nurlilasari; Rosalinda (PT SOLUSI EDUKASI BERDIKARI, 2024)
Climate change has become one of the greatest threats to the sustainability of natural resources in many regions around the world, including Gaza. Situated in the arid Middle East, Gaza faces critical water scarcity, worsened by climate change through extreme weather, reduced rainfall, rising temperatures, and infrastructure damage from conflict. This article examines the impact of climate change on Gaza's water crisis and explores how nanoparticle technology could offer an innovative solution to improve water quality and sustainability. By reviewing studies and case examples, it highlights the potential of nanoparticles in water filtration and purification, as well as the challenges of implementing this technology in Gaza. In addition, this study also presents economic solutions and integrated strategies in the context of the water resources crisis in Gaza.